The legacies of armed conflict: Insights from stayees and returning forced migrants - Isabel Ruiz; Carlos Vargas-Silva (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
How does conflict, displacement, and return shape trust, reconciliation, and community engagement? And what is the relative impact of exposure to violence on these indicators? In this paper we explore these questions by focusing on the legacies of armed conflict and the differences between those who stayed in their communities of origin during the conflict (stayees) and those who were displaced internally and internationally and who returned home over time (returnees). The results, which rely on analysis of data we collected in Burundi, suggest that internal returnees have significantly lower levels of trust, reconciliation, and community engagement than stayees, whereas the differences between international returnees and stayees are mostly statistically insignificant. Greater exposure to violence has a more positive effect on trust for returnees compared to stayees. On the other hand greater exposure to violence has a more negative effect on reconciliation and community engagement for returnees compared to stayees.
Keywords: D74; F22; Q15; R23; 330; trust; conflict; displacement